2000
DOI: 10.1177/0021886300363001
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Promotional Opportunities in Veterans Affairs Hospitals

Abstract: Pre vi ous stud ies using rela tional demog ra phy the ory have hypoth e sized that being demograph i cally dis sim i lar has a neg a tive impact on indi vid ual per cep tions of advance ment oppor tu ni ties. The authors inves ti gate whether an orga ni za tion's social con text, lead ers' char ac ter is tics, and geo graphic loca tion off set, or even reverse, the neg a tive effects of being dis sim i lar. Data were col lected through two sur veys: a 1995 sur vey of 2,252 employ ees from 139 treat ment units… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…For example, Kirchmeyer and Cohen () find that student groups who were more dissimilar, based on gender and ethnicity, used more valid assumptions to make better decisions. Lichtenstein and Alexander's () results show that the more dissimilar an employee is in age, race and gender, the more positive his or her perceptions are of advancement opportunities in their respective organizations. Pelled, Eisenhardt, and Xin () find that age similarity for work team members is positively related to emotional conflict.…”
Section: Past Research In Relational Demographymentioning
confidence: 99%
“…For example, Kirchmeyer and Cohen () find that student groups who were more dissimilar, based on gender and ethnicity, used more valid assumptions to make better decisions. Lichtenstein and Alexander's () results show that the more dissimilar an employee is in age, race and gender, the more positive his or her perceptions are of advancement opportunities in their respective organizations. Pelled, Eisenhardt, and Xin () find that age similarity for work team members is positively related to emotional conflict.…”
Section: Past Research In Relational Demographymentioning
confidence: 99%
“…We employed four items to measure perceived promotional opportunities, in which two items were adopted from Nelson, Basu, and Purdie (1998), which were found to have a reported reliability of 0.73 (Sommer & Kulkani, 2012) and additional two from Lichtenstein and Alexander (2000). On a five-point Likert scale, ranging from '1' "strongly disagree" to '5' "strongly agree," participants were asked to indicate their degree of agreement or disagreement on items like "There are insufficient opportunities for advancement in this organisation (R)" and "I do not have the opportunity to develop myself for the future (R).…”
Section: Perceived Promotional Opportunitiesmentioning
confidence: 99%
“…Conversely, other authors (e.g., Avery et al, 2008; Chatman & O'Reilly, 2004; Liao et al, 2004) have found the opposite to be the case. A third group of studies (e.g., Graves & Elsass, 2005; Lichtenstein & Alexander, 2000; Riordan & Shore, 1997) has reported mixed support or no evidence of asymmetry altogether. Thus, the empirical results, like the theoretical rationales used to predict them, conflict with one another.…”
Section: Theoretical Confusion In the Relational Demography Literaturementioning
confidence: 99%
“…One principal conclusion they drew was that Whites care more about being dissimilar than minorities. This seminal study has motivated subsequent researchers (e.g., Bacharach & Bamberger, 2004; Chattopadhyay, 1999; Lichtenstein & Alexander, 2000; Pelled, Eisenhardt, & Xin, 1999) to attempt replication of these effects and explore other instances of asymmetrical effects.…”
mentioning
confidence: 99%